Relationship Between Mothers' Knowledge Of Breastfeeding Techniques And The Incidence Of Nipple Cracking At The Telaga Dewa Health Center In Bengkulu City In 2025 - Alia Pita Sari; Yurizki Telova; Ice Rakizah Syafrie (Universitas Dehasen Bengkulu, 2026)
The postpartum period is a crucial transition period for both mother and baby, where successful breastfeeding is a key factor in supporting the health of both. One common problem experienced by postpartum mothers is sore nipples, generally caused by improper breastfeeding techniques and a lack of maternal knowledge. The purpose of this study was to determine the relationship between maternal knowledge of breastfeeding techniques and the incidence of sore nipples at the Telaga Dewa Community Health Center in Bengkulu City in 2025. This study was quantitative, using an analytical survey design. The population consisted of 57 postpartum mothers. The sampling method was accidental sampling, and data analysis was performed using the Chi-Square test. The results of the univariate analysis showed that almost half of the postpartum mothers (35.0%) had inadequate knowledge, and almost half (40.4%) had adequate knowledge. A small proportion (24.6%) had good knowledge, and the majority (56.1%) experienced sore nipples during breastfeeding. Bivariate analysis revealed a significant association between maternal knowledge of breastfeeding techniques and the incidence of sore nipples, with a p-value of 0.003 (p<0.05). Researchers recommend that postpartum mothers practice proper breastfeeding techniques to address sore nipples. Mothers can seek information about breastfeeding techniques from their local midwife or through social media.